Índices de extremos climáticos baseados na precipitação pluvial e influência de teleconexões no Nordeste do Brasil - Santos, Daris Correia dos (2019)
Northeast Brazil (NEB) is an area very vulnerable to droughts and high climatic variability, susceptible to high temperatures and irregular rains. Therefore, this study investigates the influence of global scale teleconnections that affect precipitation in the NEB, providing a better understanding of the oceanic and atmospheric effects on the internal climatic variability in order to detect changes in the precipitation pattern, based on precipitation data of 522 grid points of the Global Precipitation Climatology Centre- GPCC, 1901-2013; 512 grid points of the Tropical Rainfall Measuring Mission satellite, TRMM 3B42, from 1998-2016, and observed data from 368 meteorological stations, from the National Water Agency (ANA) and National Meteorological Institute (INMET), from 1965-2017 and data of atmospheric teleconnections from the National Centers for Environmental Prediction (NCEP). The Principal Components Analysis (PCA) extracted the most relevant variables explaining the variance of each Cluster for the spatial and temporal characterization and the Pearson coefficient investigated the degree of correlation of the climatic extremes indexes with the teleconnections, considering the levels of significance of 0.1, 0.5 and 0.01 and by means of the wavelet transform, the wavelet cross-spectrum and the wavelet coherence we detected significant periodicities. The results show that the index Days Consecutive Dry (CDD) derived from daily rainfall satellite TRMM 3B42 correlated with the Pacific Decadal Oscillation (PDO), Multidecadal Atlantic Oscillation (AMO), Southern Oscillation Index (SOI), Multivariate Index ENSO (MEI) and Niño Niño Index (ONI) indicate the increase of drought periods in NEB. In shorter periods, the local convection, homogeneous regions in the most favorable periods of drought, is strongly impacted by the Quasi-Biennial Oscillation (QBO) and Antarctica Oscillation (AAO); and the homogeneous regions most susceptible to extreme precipitation, are impacted by SOI, Tropical North Atlantic (TNAI) and Tropical South Atlantic (TSAI). The annual precipitation in wet days (PRCPTOT) from the GPCC suggests that the climatic variability of the NEB is modulated by the PDO + AMO acting simultaneously in the cold phase. The observed data shows that the most propitious areas suffer drought brunt of the AAO and Index of Global Temperature Land-Ocean (LOTI). Wavelet analysis identified significant periodicities between coupling indexes of climatic extremes and oceanic and atmospheric patterns indicating changes in climatic indexes and climatic variability of the Pacific and Atlantic Ocean and also influence of external forces in the evolution of climatic patterns in areas susceptible to events in the NEB. The Anomalies of the Sea Surface Temp (SST) in the Niño indices present great variability in the periodicity cycles of the climatic conditions in the Equatorial Pacific and influence the variability of deep tropical convection and atmospheric circulation. Finally, this information becomes useful for improvements in long-term climate predictions; implementation of strategies for adaptation and mitigation of extreme events, such as droughts and floods and agricultural planning.